Parents Just Don't Understand: Parent-Offspring Conflict over Mate Choice - Shelli L. Dubbs; Abraham P. Buunk (Evolutionary Psychology, 2010)
Previous research reveals that children and parents are not in complete agreement over which traits are most important for the mate of the child. Children tend to prefer traits that suggest genetic quality, whereas parents prefer characteristics that suggest high parental investment and cooperation with the ingroup. Using a sample of parents, mothers ( n = 234) and fathers ( n =240) the hypothesis was supported; parents perceived characteristics indicating a lack of genetic quality as being more unacceptable to the child, while characteristics indicating a lack of parental investment and cooperation with the ingroup were more unacceptable to themselves. Sex differences between mothers and fathers and sons and daughters were explored.